Reflection of parallel rays by a two-dimensional body of nearly maximal resistance - Gouveia, Paulo D.F. (2010)
This Demonstration shows a class of nonconvex bodies that maximize resistance as they move forward while slowly rotating through a rarefied medium. This class of shapes yields a resistance very close to the theoretical maximum, improving all previous results found by the authors.